Blind wayfinding with physically-based liquid sounds. Issue 115 (July 2018) - Spagnol, Simone; Hoffmann, Rebekka; Herrera Martínez, Marcelo; Unnthorsson, Runar
Highlights: A sensory substitution algorithm based on a liquid sound model is proposed. The algorithm is tested in a blind wayfinding experiment with 14 participants. Results indicate superior navigation accuracy compared to the vOICe algorithm. The delivered sounds are positively rated as intuitive and pleasant. The results should be applied to the visually impaired population with caution. Abstract: Translating visual representations of real environments into auditory feedback is one of the key challenges in the design of an electronic travel aid for visually impaired persons. Although the solutions currently available in the literature can lead to effective sensory substitution, high commitment to an extensive training program involving repetitive sonic patterns is typically required, undermining their use in everyday life. The current study explores a novel sensory substitution algorithm that extracts information from raw depth maps and continuously converts it into parameters of a naturally sounding, physically based liquid sound model describing a population of bubbles. This approach is tested in a simplified wayfinding experiment with 14 blindfolded sighted participants and compared against the most popular sensory substitution algorithm available in the literature – the vOICe (Meijer, 1992) – following a short-time training program. The results indicate a superior performance of the proposed sensory substitution algorithm in terms of navigation accuracy, intuitiveness and pleasantness of the delivered sounds compared to the vOICe algorithm. These results should be applied to the visually impaired population with caution.